2012
DOI: 10.4103/1119-3077.100623
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of lipids, total antioxidants, and trace metals in benign prostate hyperplasia and prostate cancer

Abstract: Prior to prostate biopsy, serum lipid (especially, fasting triglycerides, total cholesterol) could help in early discrimination of patients with BPH from prostate cancer in adjunct to total PSA and other management protocol for diagnosis of prostate cancer. The use of trace metal or antioxidants may have limited advantages. Further studies in this regard will be very desirable to see if this pattern of triglyceride and total cholesterol values in BPH and Pca are sustainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(22 reference statements)
3
11
0
Order By: Relevance
“…In 2009, Oluyemi et al, [32] reported a similar finding with individual antioxidants such as superoxide dismutase, catalase and vitamin E which was also supported by the observations made by Sosanya et al, (2014) [33]. Meanwhile, from an earlier study we suggested that the reason for which there was no significant difference in the level of total antioxidant status was probably because subjects took enough antioxidants that protected them from oxidative stress as at the period of study [34]. The report of this research however differ from the hypothesis advocated by Gago-Dominguez et al, (2005) [26] supporting a deficiency in lipid peroxidation and increased antioxidants as a procarcinogenic factor.…”
Section: Discussionsupporting
confidence: 70%
“…In 2009, Oluyemi et al, [32] reported a similar finding with individual antioxidants such as superoxide dismutase, catalase and vitamin E which was also supported by the observations made by Sosanya et al, (2014) [33]. Meanwhile, from an earlier study we suggested that the reason for which there was no significant difference in the level of total antioxidant status was probably because subjects took enough antioxidants that protected them from oxidative stress as at the period of study [34]. The report of this research however differ from the hypothesis advocated by Gago-Dominguez et al, (2005) [26] supporting a deficiency in lipid peroxidation and increased antioxidants as a procarcinogenic factor.…”
Section: Discussionsupporting
confidence: 70%
“…Selenium intake may be low or might have been used up in the biochemical activity of glutathione peroxidase (GPx), which keeps at bay the generated free radicals to prevent oxidative stress recently implicated in prostate carcinogenesis. [30] This finding is consistent with a recent study by Adedapo et al, [31] on biochemical tie breaker between benign prostatic hyperplasia and prostate cancer subjects, selenium showed no significant difference between the two groups. Knekt et al [32] indicated no association between selenium level and prostate cancer risk.…”
Section: Resultssupporting
confidence: 91%
“…Our result was in consonance with the findings of Nomura et al that there was no clear association between serum -tocopherol level and prostate cancer risk in a nested case-control study of Japanese-American men. [22] This observation was also reported by Adedapo et al [31] stating no significant variation between -tocopherol and prostate cancer. However, it was noted from the literatures that significant difference was observed consistently among smokers where free radicals generated reduced antioxidant status in advanced prostate cancer.…”
Section: Resultssupporting
confidence: 78%
“…Of the five measured elements, a significant difference was noticed in the concentration of Se and Zn only between PCa and BPH groups. While higher levels of Fe and Cu have been reported in diet [14], studies noted an insignificant difference in the levels of these elements in prostatic tissue [10,12], blood [15] and hair [16] of PCa patients as [17] showed significantly lower Se levels in PCa and BPH both (vs. normal prostatic tissue) with more significant decrease in case of cancer. In contrast, Zachara et al [18] found significantly (p \ 0.01) higher Se level in PCa as compared to both healthy controls and benign prostate hyperplasia.…”
Section: Discussionmentioning
confidence: 99%